BEBAS STUNTING DENGAN FLASH CARD CEGAH STUNTING PADA CALON PENGANTIN - Ulya, Ni'matul; Baroroh, Ida (POLTEKKES KEMENKES SEMARANG, 2025)
Stunting is a condition of growth failure caused the accumulation of nutritional deficiencies over a long period of time, starting from pregnancy to 24 months of age. Based on the 2022 Indonesian Nutritional Status Survey Data, the stunting rate in Central Java was recorded at 20.8%, approaching the national average 21.6%. To prevent stunting, one effort that can be made for prospective brides is utilizing the ABCDE stunting prevention card. This study used an experimental design with pretest-posttest. The population studied were all prospective brides at the Pekalongan City KUA and sample of 52 respondents was taken through a purposive sampling technique. For data collection, a questionnaire instrument was used which was given before and after treatment. Data analysis was carried out using a paired t-test. The results of the paired t-test showed a significant difference between the results before and after treatment as reflected in the Sig. (2-tailed) = 0.000 which means an increase in the knowledge of prospective brides regarding Stunting with the ABCDE flash card. Prospective brides and grooms are advised to prevent stunting early on by planning their pregnancy well, having regular pregnancy check-ups, consuming iron and good nutrition during pregnancy.